Formation of a territory: the production process of the urban space of São Bernardo do Campo/SP - Godoy , Jeane Aparecida Rombi de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
This article presents some aspects that guided the dynamics of the process of urban occupation of the protection spaces in the springs of the Billings Dam. In this region, the connection between the accelerated process of industrialization, disorderly urbanization, and the increase in population concentration over the years, devoid of adequate actions of planning and territorial ordering, contributed to the intensification of socio-spatial inequalities sustained by a pattern of exploitation and dilapidation of uses and degradation of ecosystems. From this framework, it analysed the occupation of the urban territory of São Bernardo do Campo, especially about the influence of industrialization, disorderly urbanization, and occupation of environmentally fragile areas, as well as sought to contextualize the need for new mechanisms of territorial planning and management to mitigate and reverse the high levels of biophysical vulnerability existing in the fragile spaces of protection of water sources. The approach adopted involved the analysis of data and information from various sources, such as previous studies, technical reports, municipal plans, and other relevant publications. It is hoped that the results found can subsidize the development of new studies, as well as contribute to the formulation of urban and environmental public policies.
Keywords: spatial planning; urban occupation; urbanization; water source areas; public policies